Membangun Budaya Literasi Melalui Pojok Baca di SDN Wonokusumo V/44 Surabaya - Zumaroh (PARADIGMA: JURNAL PEMIKIRAN DAN PENELITIAN PENDIDIKAN, 2025)
This article investigates the effectiveness of reading corners in enhancing literacy culture in schools. Using a case study approach, this research finds that well-implemented reading corners can significantly increase students' reading interest and literacy skills. The success of reading corners is supported by factors such as comfortable space design, diverse book collections, and active participation and support from teachers and school staff. The findings of this study emphasize the importance of integrating reading corners as an effective strategy for building a strong literacy culture among students. The contributions of this research are threefold. First, it strengthens empirical evidence that reading corners effectively enhance students' reading interest and literacy skills, contributing to our understanding of how well-designed learning environments can influence literacy behaviors. Second, it encourages educators and school decision-makers to implement reading corners as a concrete strategy for fostering a positive literacy culture, highlighting the critical role of teacher and staff support. Third, it provides practical guidelines for designing effective reading corners, including considerations for space design, diverse book collections, and strategies for managing and promoting these spaces. Future research opportunities include exploring the long-term effects of reading corners on students' literacy skills, investigating comparative studies across different school contexts to identify factors that contribute to successful reading corners, and examining the impact of reading corners on overall learning motivation. Further studies can also delve into the role of administrative support and school policies in enhancing the success of reading corners and strategies for increasing participation and engagement from the entire school community. This research lays a strong foundation for further studies in the field of literacy education, focusing on how structured learning environments can improve educational quality and student learning outcomes comprehensively